AMOFs porous carbon wave-absorbing material loaded with rare earth metal La and preparation method thereof
The preparation of La-loaded AMOFs porous carbon material addresses low energy content and porous structure issues by combining rare earth metals with MOFs, achieving enhanced electromagnetic wave absorption and stability.
Patent Information
- Application Number
- CN202411125022.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-16
- Publication Date
- 2024-12-24
AI Technical Summary
Existing absorbing materials face issues such as low energy content, lack of porous structure after carbonization, and inadequate electromagnetic wave dissipation, leading to suboptimal performance.
A method for preparing La-loaded AMOFs porous carbon absorbing material involves synthesizing a zinc-based MOF precursor with 5-methyltetrazole, loading lanthanum cations, and carbonizing at controlled temperatures to create a porous structure with enhanced magnetic and dielectric loss capabilities.
The resulting material exhibits improved electromagnetic wave absorption performance through synergistic magnetic and dielectric losses, broadband absorption, and increased thermal and chemical stability, leveraging the unique properties of rare earth metals and MOF structures.
Smart Images

Figure CN119176539A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of rare earth porous carbon wave absorbing materials, and in particular relates to an AMOFs porous carbon wave absorbing material loaded with rare earth metal La and a preparation method thereof. Background Art
[0002] Absorbing materials can effectively absorb and attenuate electromagnetic waves, prevent the impact of electromagnetic interference on electronic equipment, and thus improve the reliability and stability of the equipment. Efficient absorbing materials can be used to shield and absorb electromagnetic waves in daily life and protect human health. The demand for absorbing materials stems from the development of modern science and technology and industry. They play an important role in electronic equipment, electromagnetic shielding, military stealth, wireless communications, health protection, etc. With the advancement of science and technology and the continuous expansion of application fields, the demand for efficient, broadband, lightweight and multifunctional absorbing materials will continue to grow. Therefore, developing new absorbing materials, improving their performance, and meeting diverse application needs are important research directions in the current field of materials science and engineering.
[0003] In the field of absorbing materials, the materials that have been studied more maturely include ferrite absorbing materials, carbon silicon-based absorbing materials, conductive polymer absorbing materials, magnetic nano-absorbing materials, etc., but they each have some disadvantages and limitations, which restrict their wide application. The doping strategy of rare earth elements is considered to be the most important application method. Rare earth metals have unique electronic structures and magnetism. Rare earth metal La has incomparable advantages in breaking through the Snoek limit and enhancing high-frequency magnetic consumption due to its strong magnetic permeability and high thermal and chemical stability. It has been widely studied and applied in absorbing materials.
[0004] The document with application number "202310925210.0" discloses "a MOF-derived multi-rare earth-based composite absorbing material and its preparation method". The general formula of the composite absorbing material is Rey M1-y / carbon skeleton, wherein 0.5<y<0.8; wherein Re includes any two or at least three of Y, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm or Yb; M includes any one of Co, Ni, Cr or Fe. The problems are: 1. The content of rare earth metal salt is not appropriate: the content of rare earth metals in the multi-rare earth metal salt in this scheme is unreasonable, and there is a problem of being too low or too low. Due to different ionic radii, the specific surface area of the crystalline particles will change, resulting in a decrease in the absorption intensity of the absorbing performance. 2. The amount of linker added is unreasonable: the amount of linker added in this case is too little, which will lead to a reduction in MOF skeleton molecules, a reduction in the formed crystalline particles, and a decrease in the absorbing performance.
[0005] The document with application number "202410071438.2" discloses "a method for preparing a NiFe@C core-shell structure absorbing material and corresponding materials". A precursor solution is prepared by nickel salt, ferric chloride hexahydrate, terephthalic acid, N,N-dimethylformamide, and sodium hydroxide, and the obtained precursor solution is subjected to a hydrothermal reaction. The hydrothermal reaction product is washed and dried to obtain a NiFe metal organic framework precursor powder; a methanol solution of zinc nitrate is prepared and a prepared methanol solution of 2-methylimidazole is added to obtain a zeolite imidazole framework-8 suspension; the NiFe metal organic framework precursor powder and a surfactant are dispersed in a methanol solution to obtain a solution E; solution E is mixed and added to the zeolite imidazole framework-8 suspension, and the precipitate is washed and dried after standing to obtain a NiFe@ZI F-8 dual MOF product; the NiFe@ZI F-8 dual MOF is carbonized in an inert gas environment to obtain a NiFe@C core-shell structure absorbing material. The problems are: 1. The two MOFs used, NiFe metal organic framework, do not contain nitrogen-nitrogen double bonds, and ZI F-8 synthesis uses 2-methylimidazole diazole, which has low energy content and will not form a porous structure after carbonization, so electromagnetic waves dissipate less inside the material. 2. The carbonization temperature needs to be controlled more precisely. Too low a temperature will result in insufficient graphitization and poor comprehensive wave absorption performance. Summary of the invention
[0006] The purpose of the present invention is to provide a method for preparing La-loaded AMOFs porous carbon absorbing material to solve the problems in the prior art of low energy content, no porous structure formed after carbonization, low electromagnetic wave dissipation inside the material, and no significant improvement in absorbing performance.
[0007] In order to achieve the above object, the technical solution adopted by the present invention is a method for preparing an AMOFs porous carbon absorbing material loaded with rare earth metal La, and the specific operation steps are as follows:
[0008] Step 1, preparing AMOFs precursor: dissolving zinc nitrate, 1,4-phthalic acid, and 5-methyltetrazolyl in N,N-dimethylformamide in a certain mass ratio, mixing evenly, dropping tetramethylammonium hydroxide solution, then placing in a reactor and sealing for hydrothermal reaction, washing with N,N-dimethylformamide and ethanol to obtain needle-shaped crystals;
[0009] Step 2, dissolving lanthanum nitrate in a solvent, and after it is completely dissolved, placing needle-shaped crystals therein according to a certain mass ratio and stirring to obtain a paste slurry;
[0010] Step 3, drying the paste slurry and grinding it with an agate mortar to obtain a precursor powder;
[0011] Step 4: Place the precursor powder in a tube furnace under an inert atmosphere, heat it to 800-1000° C., keep it warm for 2-3 hours, and then cool it naturally to room temperature to obtain an AMOFs porous carbon absorbing material loaded with rare earth metal La.
[0012] Furthermore, in the above step 1, the mass ratio of zinc nitrate, 1,4-phthalic acid and 5-methyltetrazolyl is 10:6:3.
[0013] Furthermore, in the above step 1, the hydrothermal reaction temperature is set between 80°C and 120°C, and the reaction time is 36 to 60 hours.
[0014] Furthermore, in the above step 2, the mass ratio of lanthanum nitrate to needle-shaped crystal A is 1:4.
[0015] Furthermore, the stirring time in the above step 2 is 24 to 48 hours.
[0016] Furthermore, in the above step 2, the solvent is methanol, ethanol or diethyl ether.
[0017] Furthermore, in the above step 3, the temperature of the blast drying oven is 60-80° C., and the time is 24-48 hours.
[0018] Furthermore, in the above step 4, the inert gas is argon, helium or nitrogen.
[0019] Furthermore, in the above step 4, the heating rate is 5-10°C / min.
[0020] Furthermore, the above preparation method obtains an AMOFs porous carbon absorbing material loaded with rare earth metal La.
[0021] Compared with the prior art, the advantages of the present invention are:
[0022] 1. The porous carbon material loaded with rare earth metal La prepared by the method is an anionic metal organic framework (Anionic Metal-Organic Frameworks), which is negatively charged and can load cations on the active sites in the pores. AMOF has high selectivity for positively charged substances and is used for the separation and enrichment of specific cations. The present invention captures rare earth metal cations through the ion exchange mechanism of the anionic metal organic framework, and converts La 3+ Combined with the active sites in AMOFS, the advantages of both are combined to produce a synergistic effect, further improving the material's microwave absorption performance. The specific analysis of the synergistic effect is as follows:
[0023] (1) The rare earth metal lanthanum has strong magnetism, which helps to improve the magnetic loss capacity of the material. The organic skeleton and metal nodes of the MOF material can provide good dielectric loss performance. The combination of the two can achieve the synergistic effect of magnetic loss and dielectric loss, thereby improving the material's ability to absorb electromagnetic waves.
[0024] (2) A single material may have limitations in the absorption band, but by combining rare earth metals with MOF materials, the effective working band of the absorbing material can be expanded. The multiple valence states and complex electronic structures of rare earth metals can be combined with the structural characteristics of MOF materials to form a composite material with broadband absorption characteristics.
[0025] (3) MOF materials may have stability problems in high temperature and chemical environment, while rare earth metals generally have good thermal stability and chemical stability. By incorporating rare earth metals into MOF materials, the carbon material formed after heat treatment is a porous structure with an ultra-high specific surface area, which is conducive to the multiple scattering of electromagnetic waves inside the material, improves the dissipation capacity, and can significantly improve the thermal stability and chemical stability of the composite material, thereby enhancing its reliability in practical applications. 2. The present invention adopts an environmentally friendly, simple, green, and controllable hydrothermal chemical synthesis method to prepare AMOFs materials, and introduces polynitrogen azoles of 5-methyltetrazole during the preparation process. The synthesized MOF ligand uses 5-methyltetrazole with a high nitrogen content. There are a large number of nitrogen-nitrogen double bonds in MOF, and the cleavage of nitrogen-nitrogen bonds can release a large amount of energy. Therefore, in the subsequent carbonization process, the morphology and performance of the product are regulated by the high energy generated by the cleavage of the nitrogen-nitrogen double bond at 400°C, so that the material of the present invention forms a porous structure, which is conducive to the multiple scattering of electromagnetic waves inside the material. The pores in the porous carbon material provide abundant paths for the propagation of incident electromagnetic waves, which is conducive to the multiple losses of electromagnetic waves inside the material. Then, by loading the rare earth metal cation lanthanum, the magnetic permeability of the target material is effectively improved, and through the synergistic effect of multiple loss mechanisms in the material, an ideal electromagnetic wave absorption material is obtained. The preparation method first prepares the zinc-based MOF MOZ-200 containing polynitrogen azoles, and then loads metal ions. It has strong controllability, easy operation, high production efficiency and short time.
[0026] 3. The present invention synthesizes porous carbon absorbing materials through the following key steps:
[0027] (I) Synthesis of AMOFs precursor: The precursor needle-shaped crystal is a high-porosity precursor AMOF material, which is rich in zinc-based tetrazole energetic AMOF. During the subsequent heat treatment process, the Zn nodes are reduced and volatilized, while the high-energy nitrogen-nitrogen double bonds decompose and release a large amount of heat and nitrogen, making the carbon material form a porous structure, providing a rich path for the propagation of incident electromagnetic waves.
[0028] (II) AMOFs loaded with rare earth metal cations La 3+ :A simple and controllable mechanical stirring operation method was used to introduce La 3+ During the stirring process, mechanical activation is used to promote La 3+ Chemical adsorption and chemical reaction in the active sites of the AMOF pores. Selecting the appropriate amount of rare earth metal loading to achieve optimal control of the material's magnetic permeability and impedance matching can not only ensure that the amount of rare earth metal is sufficient to form effective magnetic loss and dielectric loss centers, but also maintain the structural stability of AMOFs, so that the porous structure of the material will not collapse and form a uniform particle distribution, thereby improving the wave absorption performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 Flow chart of the preparation method of the porous carbon absorbing material of the present invention;
[0030] Figure 2 The metal cation La in Example 1 3+ XRD diffraction pattern of anionic framework AMOFs precursor material;
[0031] Figure 3 is the SEM image of Example 1;
[0032] Figure 4 is a reflection loss diagram of Example 1;
[0033] Figure 5 is a bandwidth diagram of Example 1;
[0034] Figure 6 is a real part diagram of dielectric loss of Example 1;
[0035] Figure 7 is a graph of the imaginary part of dielectric loss of Example 1;
[0036] Figure 8 is a dielectric loss tangent diagram of Example 1;
[0037] Fig. 9 is a real part diagram of magnetic loss of Example 1;
[0038] Fig.10 is the imaginary part diagram of magnetic loss of Example 1;
[0039] Fig.11 is the magnetic loss tangent diagram of Example 1;
[0040] Fig.12 is a reflection loss diagram of Example 2;
[0041] Fig.13 is a reflection loss diagram of Example 3;
[0042] Fig.14 is a reflection loss diagram of Example 4;
[0043] Fig.15 It is a reflection loss diagram for comparison. DETAILED DESCRIPTION
[0044] The present invention will be further described below in conjunction with specific embodiments and drawings.
[0045] The preparation principle of the present invention is as follows: Figure 1 As shown in the figure, a high-energy AMOF rich in zinc-based tetrazolyl was first synthesized by hydrothermal method as a precursor. Due to its extremely high specific surface area and designability, the organic skeleton contains a rich carbon source, which provides a basis for synthesizing porous carbon composite materials by heat treatment. After loading rare earth metal lanthanum using physical mixing method, porous carbon materials were obtained by high-temperature carbonization.
[0046] Example 1, a method for preparing an AMOFs porous carbon absorbing material loaded with rare earth metal La, the specific steps are as follows:
[0047] Step 1: Prepare the AMOFs precursor using a hydrothermal method: dissolve 0.296 g of zinc nitrate, 0.166 g of 1,4-phthalic acid, and 0.084 g of 5-methyltetrazole in 10 ml of N,N-dimethylformamide, mix well, then drop 0.2 ml of about four drops of tetramethylammonium hydroxide solution, then put it into a 25 ml Teflon reactor and seal it, place it in a 120 ° C forced air drying oven to react for 36 hours, and wash it with N,N-dimethylformamide and ethanol to obtain needle-shaped crystals;
[0048] Step 2: Dissolve 0.233 g of lanthanum nitrate in 4 ml of methanol. After it is completely dissolved, add 1 g of needle-shaped crystals and stir for 48 hours to obtain a paste slurry.
[0049] Step 3, placing the paste slurry in a 60° C. forced air drying oven for 48 hours to completely evaporate the solvent, and grinding it with an agate mortar to obtain a precursor powder;
[0050] Step 4: Place the precursor powder in a porcelain boat, place it in a program-controlled temperature tube furnace under the protection of a N2 atmosphere, heat it to 1000°C at a heating rate of 10°C / min, keep it warm for 2 hours, and then cool it naturally to room temperature to obtain a black powder, i.e., an AMOFs porous carbon absorbing material loaded with rare earth metal La.
[0051] Example 2, a method for preparing an AMOFs porous carbon absorbing material loaded with rare earth metal La, the specific steps are as follows:
[0052] Step 1: Prepare the AMOFs precursor using a hydrothermal method: dissolve 0.296 g of zinc nitrate, 0.166 g of 1,4-phthalic acid, and 0.084 g of 5-methyltetrazole in 10 ml of N,N-dimethylformamide, mix well, then drop 0.2 ml of about four drops of tetramethylammonium hydroxide solution, then put it into a 25 ml Teflon reactor and seal it, place it in a 100 ° C forced air drying oven to react for 60 hours, and wash it with N,N-dimethylformamide and ethanol to obtain needle-shaped crystals;
[0053] Step 2: dissolve 0.7 g of lanthanum nitrate in 4 ml of methanol, and after it is completely dissolved, place 1 g of needle-shaped crystals therein and stir for 48 hours to obtain a paste slurry;
[0054] Step 3, placing the paste slurry in a forced air drying oven at 80° C. for 40 hours to completely evaporate the solvent, and grinding it with an agate mortar to obtain a precursor powder;
[0055] Step 4: Place the precursor powder in a porcelain boat, place it in a program-controlled temperature tube furnace under the protection of a N2 atmosphere, heat it to 1000°C at a heating rate of 5°C / min, keep it warm for 2 hours, and then cool it naturally to room temperature to obtain a black powder, i.e., an AMOFs porous carbon absorbing material loaded with rare earth metal La.
[0056] Example 3, a method for preparing an AMOFs porous carbon absorbing material loaded with rare earth metal La, the specific steps are as follows:
[0057] Step 1: Prepare the AMOFs precursor using a hydrothermal method: dissolve 0.296 g of zinc nitrate, 0.166 g of 1,4-phthalic acid, and 0.084 g of 5-methyltetrazole in 10 ml of N,N-dimethylformamide, mix well, then drop 0.2 ml of about four drops of tetramethylammonium hydroxide solution, then put it into a 25 ml Teflon reactor and seal it, place it in a 120 ° C forced air drying oven to react for 50 hours, and wash it with N,N-dimethylformamide and ethanol to obtain needle-shaped crystals;
[0058] Step 2: Dissolve 0.233 g of lanthanum nitrate in 4 ml of methanol. After it is completely dissolved, add 1 g of needle-shaped crystals and stir for 48 hours to obtain a paste slurry.
[0059] Step 3, placing the paste slurry in a 60° C. forced air drying oven for 48 hours to completely evaporate the solvent, and grinding it with an agate mortar to obtain a precursor powder;
[0060] Step 4: Place the precursor powder into a porcelain boat, place it in a program-controlled temperature tube furnace under the protection of a N2 atmosphere, heat it to 800°C at a heating rate of 10°C / min, keep it warm for 2 hours, and then cool it naturally to room temperature to obtain a black powder, i.e., an AMOFs porous carbon absorbing material loaded with rare earth metal La.
[0061] Example 4, a method for preparing an AMOFs porous carbon absorbing material loaded with rare earth metal La, the specific steps are as follows:
[0062] Step 1: Prepare the AMOFs precursor using a hydrothermal method: dissolve 0.296 g of zinc nitrate, 0.166 g of 1,4-phthalic acid, and 0.084 g of 5-methyltetrazole in 10 ml of N,N-dimethylformamide, mix well, then drop 0.2 ml of about four drops of tetramethylammonium hydroxide solution, then put it into a 25 ml Teflon reactor and seal it, place it in a 120 ° C forced air drying oven to react for 36 hours, and wash it with N,N-dimethylformamide and ethanol to obtain needle-shaped crystals;
[0063] Step 2: Dissolve 0.233 g of lanthanum nitrate in 4 ml of methanol. After it is completely dissolved, add 1 g of needle-shaped crystals and stir for 24 hours to obtain a paste slurry.
[0064] Step 3, placing the paste slurry in a forced air drying oven at 80° C. for 48 hours to completely evaporate the solvent, and grinding it with an agate mortar to obtain a precursor powder;
[0065] Step 4: Place the precursor powder into a porcelain boat, place it in a program-controlled temperature tube furnace under the protection of a N2 atmosphere, heat it to 900°C at a heating rate of 10°C / min, keep it warm for 3 hours, and then cool it naturally to room temperature to obtain a black powder, i.e., an AMOFs porous carbon absorbing material loaded with rare earth metal La.
[0066] Comparative Example
[0067] A method for preparing an AMOFs porous carbon absorbing material, the specific steps are as follows:
[0068] Step 1, dissolving 0.296 g of zinc nitrate, 0.166 g of 1,4-phthalic acid, and 0.084 g of 5-methyltetrazole in N,N-dimethylformamide, and dropping four drops of tetramethylammonium hydroxide solution into the mixture after mixing evenly, and then placing the mixture in a 25 ml Teflon reactor and sealing it, placing it in a 100° C. forced drying oven to react for 48 hours, and washing it with N,N-dimethylformamide and ethanol to obtain needle-shaped crystals A;
[0069] Step 2: Place the needle-shaped crystal A into a porcelain boat, place it in a program-controlled temperature tube furnace under the protection of a N2 atmosphere, heat it to 1000°C at a heating rate of 10°C / min, keep it warm for 3 hours, and then naturally cool it to room temperature to obtain a black powder.
[0070] The black powder and paraffin prepared in Examples 1-4 and the comparative example were mixed in a mass ratio of 20:80, and then pressed into ring-shaped samples for testing the reflection loss performance of the samples.
[0071] like Figure 2 As shown, the XRD diffraction pattern proves the successful synthesis of the La-loaded anion framework precursor material.
[0072] like Figure 3 The figure shows a SEM image of the AMOFs porous carbon absorbing material loaded with rare earth metal La according to the present invention. It can be seen from the figure that the absorbing material has a rich porous structure.
[0073] like Figure 4 As shown, it is a reflection loss diagram of the AMOFs porous carbon absorbing material loaded with rare earth metal La in the frequency band of 2 to 18 GHz. The absorber has the best reflection loss when the thickness is 3.5 mm, and the minimum reflection loss value is -50.49 dB.
[0074] like Figure 5 As shown, it is a bandwidth diagram of the AMOFs porous carbon absorbing material loaded with rare earth metal La in the frequency band of 2 to 18 GHz. When the thickness is 2 mm, the effective absorbing bandwidth less than -10 dB reaches 3.52 GHz.
[0075] like Figure 6 As shown, this is the real part diagram of the dielectric loss of the AMOFs porous carbon absorbing material loaded with rare earth metal La in the frequency band of 2 to 18 GHz. The absorption capacity decreases with increasing frequency, and the initial real part value is relatively high, indicating that the material has good storage capacity, reaching a minimum value at 11.5 GHz, indicating that the electrical storage effect is the smallest and the dissipation effect is the largest here.
[0076] like Figure 7 As shown, it is the imaginary part diagram of the dielectric loss of the AMOFs porous carbon absorbing material loaded with rare earth metal La in the frequency band of 2 to 18 GHz. As the frequency increases, the loss capacity shows a trend of first decreasing and then increasing.
[0077] like Figure 8 As shown, it is the dielectric loss tangent diagram of the AMOFs porous carbon absorbing material loaded with rare earth metal La in the frequency band of 2 to 18 GHz, representing the capacity of electrical loss.
[0078] like Fig. 9As shown, it is the real part diagram of the magnetic loss of the AMOFs porous carbon absorbing material loaded with rare earth metal La in the frequency band of 2 to 18 GHz. A higher real part value means that the material can respond to the external magnetic field more effectively and can better store magnetic energy.
[0079] like Fig.10 As shown, it is the imaginary part diagram of the magnetic loss of the AMOFs porous carbon absorbing material loaded with rare earth metal La in the frequency band of 2 to 18 GHz. A higher imaginary part value means that the material loses more energy under the action of the magnetic field.
[0080] like Fig.11 As shown, it is the magnetic loss tangent diagram of the AMOFs porous carbon absorbing material loaded with rare earth metal La in the frequency band of 2 to 18 GHz, representing the capacity of magnetic loss.
[0081] like Fig.12 As shown, it is a reflection loss diagram of Example 2 in the 2-18 GHz frequency band. The minimum reflection loss value of this example is -30.26 dB when the thickness is 5 mm.
[0082] like Fig.13 As shown, it is a reflection loss diagram of Example 3 in the frequency band of 2 to 18 GHz. The minimum reflection loss value of this example is -22.71 dB when the thickness is 4 mm.
[0083] like Fig.14 As shown, it is a reflection loss diagram of Example 4 in the frequency band of 2 to 18 GHz. The minimum reflection loss value of this example is -19.70 dB when the thickness is 5 mm.
[0084] like Fig.15 As shown, it is a reflection loss diagram of the comparative example in the frequency band of 2 to 18 GHz. The minimum reflection loss value of this example is -6.20 dB when the thickness is 3 mm.
[0085] In summary, embodiment 1 is the best embodiment.
[0086] The above is an explanation of the specific implementation of the present invention, rather than a limitation of the present invention. Those skilled in the relevant technical field can also make various equivalent technical solutions without departing from the scope of the present invention, so all equivalent technical solutions should be included in the patent protection scope of the present invention.
Claims
1. A method for preparing an AMOFs porous carbon absorbing material loaded with rare earth metal La, characterized in that: The specific steps are as follows: Step 1, preparing AMOFs precursor: dissolving zinc nitrate, 1,4-phthalic acid, and 5-methyltetrazolyl in N,N-dimethylformamide in a certain mass ratio, mixing evenly, dropping tetramethylammonium hydroxide solution, then placing in a reactor and sealing for hydrothermal reaction, washing with N,N-dimethylformamide and ethanol to obtain needle-shaped crystals; Step 2, dissolving lanthanum nitrate in a solvent, and after it is completely dissolved, placing needle-shaped crystals therein according to a certain mass ratio and stirring to obtain a paste slurry; Step 3, drying the paste slurry and grinding it with an agate mortar to obtain a precursor powder; Step 4: Place the precursor powder in a tube furnace under an inert atmosphere, heat it to 800-1000° C., keep it warm for 2-3 hours, and then cool it naturally to room temperature to obtain an AMOFs porous carbon absorbing material loaded with rare earth metal La.
2. The method for preparing the AMOFs porous carbon absorbing material loaded with rare earth metal La according to claim 1, characterized in that: In the step 1, the mass ratio of zinc nitrate, 1,4-phthalic acid and 5-methyltetrazolyl is 10:6:
3.
3. The method for preparing the AMOFs porous carbon absorbing material loaded with rare earth metal La according to claim 2, characterized in that: In the step 1, the hydrothermal reaction temperature is set between 80° C. and 120° C., and the reaction time is 36 to 60 hours.
4. The method for preparing the AMOFs porous carbon absorbing material loaded with rare earth metal La according to claim 3, characterized in that: In the step 2, the mass ratio of lanthanum nitrate to needle-shaped crystal A is 1:
4.
5. The method for preparing the AMOFs porous carbon absorbing material loaded with rare earth metal La according to claim 4, characterized in that: The stirring time in step 2 is 24 to 48 hours.
6. The method for preparing the AMOFs porous carbon absorbing material loaded with rare earth metal La according to claim 5, characterized in that: The solvent in step 2 is methanol, ethanol or ether.
7. The method for preparing the AMOFs porous carbon absorbing material loaded with rare earth metal La according to claim 6, characterized in that: In the step 3, the temperature of the blast drying oven is 60-80° C. and the drying time is 24-48 hours.
8. The method for preparing the AMOFs porous carbon absorbing material loaded with rare earth metal La according to claim 7, characterized in that: In step 4, the inert gas is argon, helium or nitrogen.
9. The method for preparing the AMOFs porous carbon absorbing material loaded with rare earth metal La according to claim 8, characterized in that: The heating rate in step 4 is 5-10°C / min.
10. The method for preparing the AMOFs porous carbon absorbing material loaded with rare earth metal La according to claim 1, characterized in that: The preparation method obtains an AMOFs porous carbon wave absorbing material loaded with rare earth metal La.
